2015
DOI: 10.1016/j.rboe.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Associations of vitamin D deficiency with postoperative gait and mortality among patients with fractures of the proximal femur

Abstract: ObjectiveTo assess whether serum vitamin D concentration is associated with gait status and mortality among patients with fractures of the proximal femur, six months after suffering the fracture.MethodsConsecutive patients aged ≥65 years with fractures of the proximal femur, who were admitted to the orthopedics and traumatology ward of our service between January and December 2011, were prospectively evaluated. Clinical, radiological, epidemiological and laboratory analyses were performed, including vitamin D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…[ 19 20 21 ] However, serum vitamin D concentrations and mortality rates in elderly patients with hip fractures are rarely reported. [ 22 23 ] Although our univariate analysis found that vitamin D deficiency was an independent risk factor for mortality after hip fracture, it was not associated with mortality after adjusting for age ( P <0.001), BMI ( P =0.041), type of management ( P <0.001), ASA score ( P =0.009), pre-fracture ambulatory status ( P <0.001), and osteoporosis ( P <0.001) in the multivariate analysis. This finding is similar to a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 19 20 21 ] However, serum vitamin D concentrations and mortality rates in elderly patients with hip fractures are rarely reported. [ 22 23 ] Although our univariate analysis found that vitamin D deficiency was an independent risk factor for mortality after hip fracture, it was not associated with mortality after adjusting for age ( P <0.001), BMI ( P =0.041), type of management ( P <0.001), ASA score ( P =0.009), pre-fracture ambulatory status ( P <0.001), and osteoporosis ( P <0.001) in the multivariate analysis. This finding is similar to a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to a previous study. Gumieiro et al[ 22 ] assessed whether serum vitamin D concentration is associated with gait status and mortality among 87 elderly patients with fractures of the proximal femur 6 months after suffering the fracture. They reported that serum vitamin D concentration was not related to gait status or mortality among patients with fractures proximal femur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Browne et al, 13 using a different serum measuring unit (nmol/L) in a study in Ireland with 156 elderly patients with PFF, found that over 67% of their sample had insufficient or deficient 25(OH)D serum levels. Gumiero et al, 14 in a Brazilian study on gait in patients with PFF, also observed low levels of 25(OH)D, with a mean value of 27.8 ng/mL; 33.7% of the sample had deficient values, which differs from the findings of the present study 7, 14. Reduced serum levels of 25(OH)D were significantly related to PFF both in the present study and in previous studies; however, specific differences in serum levels of this vitamin are recognized by various authors, due to its relation to sun exposure and the genetic characteristics of the local population 11, 12, 13…”
Section: Discussionmentioning
confidence: 97%
“…In a review study, Patton et al reported that 25(OH)D levels were comparatively lower in women, regardless of the cut-off criteria used 6, 13, 14, 15, 16, 17, 18. Labronici et al, 18 when assessing post-menopausal women, found that 82% of the patients had 25(OH)D levels considered insufficient.…”
Section: Discussionmentioning
confidence: 99%